Find all School-related info fast with the new School-Specific MBA Forum

 It is currently 02 Jul 2015, 15:58

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# In a sequence, after the first two terms, each term is the

 Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:
Senior Manager
Joined: 08 Aug 2005
Posts: 251
Followers: 1

Kudos [?]: 19 [0], given: 0

In a sequence, after the first two terms, each term is the [#permalink]  21 Apr 2006, 03:17
1
This post was
BOOKMARKED
In a sequence, after the first two terms, each term is the sum of all the previous terms. If an=P, a(n+2)=?
Director
Joined: 24 Oct 2005
Posts: 660
Location: London
Followers: 1

Kudos [?]: 9 [0], given: 0

[#permalink]  21 Apr 2006, 04:33
a(1) = a
a(2) = b
a(3) = a+b
a(4) = 2a + 2b
a(5) = 4a + 4b

Let us take a(n) = a(3) = a + b = P
Therefore, a(n+ 2) = a(5) = 4(a+b) = 4P

Ans = 4P
VP
Joined: 06 Jun 2004
Posts: 1059
Location: CA
Followers: 2

Kudos [?]: 54 [0], given: 0

[#permalink]  27 Apr 2006, 20:12
Agree with remgeo's approach
_________________

Don't be afraid to take a flying leap of faith.. If you risk nothing, than you gain nothing...

Manager
Joined: 14 Mar 2006
Posts: 208
Followers: 1

Kudos [?]: 4 [0], given: 0

[#permalink]  28 Apr 2006, 06:05
remgeo wrote:
a(1) = a
a(2) = b
a(3) = a+b
a(4) = 2a + 2b
a(5) = 4a + 4b

Let us take a(n) = a(3) = a + b = P
Therefore, a(n+ 2) = a(5) = 4(a+b) = 4P

Ans = 4P

Took me a while but I think i understand your explanation.

since we let n=3, a(3)= a+b
therefore, P= a+b
Now lets look at a(n+2), since n=3 we have a(3+2)=a(5), where a(5)= 4a+4b. or 4(a+b), since P=a+b, we have 4P

I had to break it down for my understanding, plz let me know if I am wrong. greak work!
Director
Joined: 04 Jan 2006
Posts: 925
Followers: 1

Kudos [?]: 16 [0], given: 0

[#permalink]  29 Apr 2006, 08:40
Does it work for n=1?
Manager
Joined: 09 Apr 2006
Posts: 173
Location: Somewhere in Wisconsin!
Followers: 1

Kudos [?]: 2 [0], given: 0

[#permalink]  29 Apr 2006, 09:15
Probably the question is interested in all n after the first two numbers.
_________________

Thanks,
Zooroopa

[#permalink] 29 Apr 2006, 09:15
Similar topics Replies Last post
Similar
Topics:
In the sequence 1, 2, 4, 8, 16, 32, , each term after the 2 19 Sep 2008, 09:40
In a sequence of number each term is the sum of the two 1 11 Mar 2008, 07:35
In a sequence of numbers in which each term after the first 3 25 Sep 2007, 05:32
In the sequence 1,1,2,3,5,8, .. , each term after the first 4 30 Oct 2006, 19:48
In a sequence, after the first two terms, each term is the 1 21 Apr 2006, 03:16
Display posts from previous: Sort by

# In a sequence, after the first two terms, each term is the

 Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group and phpBB SEO Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.